Jak minimalizovat stopy vědeckého výzkumu?: Východní Svalbard - místo pro srovnávací výzkum - Klimešová, JItka
How to reduce scientific footprint? The climate changes have contributed to the continously growing interest for field research in Eastern Svalbard. In many research fields, the knowledge about East Svalbard is extremely limited and therefore data is needed first before it is possible to establish a baseline for future reference. To affect reference area as less as possible, data collection should leave small size footprint on environment (e.g. using advanced, non-intrusive technology, several groups working in field together in coordinated and synchronized manner).